2021
DOI: 10.3390/su13031560
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SDGs towards Coastal Management: Sustainability Performance and Cross-Linking Consequences

Abstract: The Sustainable Development Goals (SDGs) and associated targets focus on a wide range of global issues and can be useful in coastal challenges such as climate change and green economic growth. The aim of this study is to tailor the SDGs, as a universally recognized policy framework, to assess the sustainability performance for coastal flood protection management to enhance climate-resilient and adaptable coastal development. To operationalize this aim, the SDG Sustainability Impact Score (SDG-SIS) framework wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 61 publications
0
26
0
1
Order By: Relevance
“…The type of environment under consideration typically differs; Kumar et al [10], Ruangpan et al [11], Calliari et al [14], and Nesshöver et al [15] do not focus on a single environment, in contrast to many other studies wherein a specific type of environment is the focus. The environments most studied are urban, large rivers (250-300 km), and coasts [11,13,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The type of environment under consideration typically differs; Kumar et al [10], Ruangpan et al [11], Calliari et al [14], and Nesshöver et al [15] do not focus on a single environment, in contrast to many other studies wherein a specific type of environment is the focus. The environments most studied are urban, large rivers (250-300 km), and coasts [11,13,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, studies such as those by ones of Artmann et al [22], Pakzad et al [23], Raymond et al [20] showed that NBSs interact across and within society, economy, and environment. Building on that, subsequent studies (e.g., [18,21,24]) examined the potential contributions of NBSs to the UN 2030 Agenda by examining the SDGs and/or their targets. Schipper et al [21] developed the Sustainability Impact Score (SIS) Assessment Framework, which uses a selection of SDGs and SDG targets to score the sustainability performance of coastal management projects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified the correspondence between SDGs and aspects of the environment (sensu lato), including climate and ecosystems (e.g., Walmsley, 2002;Cumming et al, 2017;Nhamo, 2017;Omisore, 2018;Dawson et al, 2019) but this recognition has not followed through into meaningful developmental strategies that use environmental measures as performance indicators (Nhemachena et al, 2018;Le Roux and Pretorius, 2019;Jiménez-Aceituno et al, 2020). There is therefore a disconnection between the driving factors behind sustainable development, and the performance indicators used for monitoring achievement of SDGs (e.g., Patole, 2018;Schipper et al, 2021). This is clearly an issue for correctly identifying, enacting and monitoring the success of sustainable development strategies (Knight, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, necessary to take into account all the needs of stakeholders and ensure a better and more sustainable future for all. It is important to describe the conditions and barriers to the implementation of MDGs in freight supply chains, which reflect supply chain practices for research and performance evaluation in line with sustainable development goals [8,9].…”
Section: Literature Reviewmentioning
confidence: 99%